CRITICAL SUCCESS FACTORS FRAMEWORK IN A PROCESS APPROACH: AN INFORMATION TECHNOLOGY STRATEGIC DIRECTION SETTING APPROACH - Victor, M A.M (Tanzania Journal of Engineering and Technology, 2018)
Abstract